Fatal infectious mononucleosis in a 19-year old woman with myelodysplastic syndrome – a case report - Dytfeld, Dominik; Lewandowska, Maria; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2006)
Epstein-Barr virus is widespread in the human population, but only in some causes the usually self-limited disease named infectious mononucleosis (IM). IM is usually associated with low percentage of severe complications and does not require causal treatment. In the 19-year old patient described below, who was treated symptomatically because of myelodysplatic syndrome RARS, IM complicated with liver insufficiency, pancytopenia and lymphopenia probably due to haemophagocytic syndrome was diagnosed. Then, bronchopneumonia and treatment-resistant septic shock occurred, which eventually caused death.